"Acalypha carrascoana" Cardiel ("Euphorbiaceae") novelty for the flora of Mexico - Cardiel, José María; Muñoz-Rodríguez, Pablo (Botanica Complutensis, 2013)
Acalypha carrascoana Cardiel, only known from Colombia and Venezuela, is reported in Mexico, thus presenting a disjunct distribution. Comments on the systematic of related species of Acalypha section Sclerolobae Müll. Arg. are included. An identification key to the species of this section is also provided.
Keywords: Acalypha; Euphorbiaceae; Mexico; disjunction; species identification